The good impacts of biking for goods: Lessons from Paris city. Issue 4 (December 2016) - Koning, Martin; Conway, Alison
Highlights: Paris "pro-bikes" policies have led to a mode shift for commercial goods delivery. In 2014, 15 cycle freight firms moved about 1107 tkm daily in Paris. Annual externality savings of 0.76 M Є were estimated for 2014 compared to 2001. Main benefits arise from a reduced use of motorized two-wheels or vans and from reduced local pollutants or road congestion. Abstract: This paper seeks to assess the growing usage of bicycles and tricycles for commercial goods movement in Paris city and the resulting transport externality savings between 2001 and 2014. Results from an original survey of nine couriers and delivery companies are presented to quantify new commercial goods movements via human-powered or electrically-assisted bicycles or cargo cycles. After identifying growth in cycle freight volumes and the modes by which these trips previously moved, congestion, CO2, local pollutant, and noise savings are estimated and valued.